[Cover letter to Bob Pruett from Phil Giarizzo Campaign Consulting] - GIARRIZZO P (Tufts Archival Research Center, 2007)
Missing Attachments; Cover letter to Bob Pruett from Phil Giarizzo Campaign Consulting. Introduces letters generated in opposition to AB 13 to be faxed to all members of the Ways & Means Committee. Discusses attempts to reach hotel/restaurant employees unions.